Digital Traffic, Financial Performance, and Stock Valuation - Armstrong, Christopher S.; Konchitchki, Yaniv; Zhang, Biwen (The Accounting Review, 2025)
ABSTRACT We examine the economic implications of digital traffic on firms’ financial performance, stock valuation, and financial surprises. Our analysis shows that timely flows of digital traffic are contemporaneous and leading indicators of firms’ revenue and profitability—both gross and operating. Moreover, we show that digital traffic contains novel information about firms’ future performance that is not entirely reflected in stock prices, analyst forecasts, or historical (i.e., time series) financial metrics. Notably, digital-traffic-based investment strategies are lucrative and generate substantial abnormal returns. Importantly, we also adduce evidence that corroborates our conjecture about the underlying economic mechanism that explains the valuation implications of digital traffic: These are driven by firms with consumer-oriented websites that facilitate sale transactions. Data Availability: Data are available from the sources cited in the text. JEL Classifications: E32; G32; O33.